62058
|
1 |
(* Title: HOL/Library/Quadratic_Discriminant.thy
|
60162
|
2 |
Author: Tim Makarios <tjm1983 at gmail.com>, 2012
|
|
3 |
|
|
4 |
Originally from the AFP entry Tarskis_Geometry
|
|
5 |
*)
|
|
6 |
|
|
7 |
section "Roots of real quadratics"
|
|
8 |
|
|
9 |
theory Quadratic_Discriminant
|
|
10 |
imports Complex_Main
|
|
11 |
begin
|
|
12 |
|
|
13 |
definition discrim :: "[real,real,real] \<Rightarrow> real" where
|
|
14 |
"discrim a b c \<equiv> b\<^sup>2 - 4 * a * c"
|
|
15 |
|
|
16 |
lemma complete_square:
|
|
17 |
fixes a b c x :: "real"
|
|
18 |
assumes "a \<noteq> 0"
|
|
19 |
shows "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow> (2 * a * x + b)\<^sup>2 = discrim a b c"
|
|
20 |
proof -
|
|
21 |
have "4 * a\<^sup>2 * x\<^sup>2 + 4 * a * b * x + 4 * a * c = 4 * a * (a * x\<^sup>2 + b * x + c)"
|
|
22 |
by (simp add: algebra_simps power2_eq_square)
|
60500
|
23 |
with \<open>a \<noteq> 0\<close>
|
60162
|
24 |
have "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow> 4 * a\<^sup>2 * x\<^sup>2 + 4 * a * b * x + 4 * a * c = 0"
|
|
25 |
by simp
|
|
26 |
thus "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow> (2 * a * x + b)\<^sup>2 = discrim a b c"
|
|
27 |
unfolding discrim_def
|
|
28 |
by (simp add: power2_eq_square algebra_simps)
|
|
29 |
qed
|
|
30 |
|
|
31 |
lemma discriminant_negative:
|
|
32 |
fixes a b c x :: real
|
|
33 |
assumes "a \<noteq> 0"
|
|
34 |
and "discrim a b c < 0"
|
|
35 |
shows "a * x\<^sup>2 + b * x + c \<noteq> 0"
|
|
36 |
proof -
|
|
37 |
have "(2 * a * x + b)\<^sup>2 \<ge> 0" by simp
|
60500
|
38 |
with \<open>discrim a b c < 0\<close> have "(2 * a * x + b)\<^sup>2 \<noteq> discrim a b c" by arith
|
|
39 |
with complete_square and \<open>a \<noteq> 0\<close> show "a * x\<^sup>2 + b * x + c \<noteq> 0" by simp
|
60162
|
40 |
qed
|
|
41 |
|
|
42 |
lemma plus_or_minus_sqrt:
|
|
43 |
fixes x y :: real
|
|
44 |
assumes "y \<ge> 0"
|
|
45 |
shows "x\<^sup>2 = y \<longleftrightarrow> x = sqrt y \<or> x = - sqrt y"
|
|
46 |
proof
|
|
47 |
assume "x\<^sup>2 = y"
|
|
48 |
hence "sqrt (x\<^sup>2) = sqrt y" by simp
|
|
49 |
hence "sqrt y = \<bar>x\<bar>" by simp
|
|
50 |
thus "x = sqrt y \<or> x = - sqrt y" by auto
|
|
51 |
next
|
|
52 |
assume "x = sqrt y \<or> x = - sqrt y"
|
|
53 |
hence "x\<^sup>2 = (sqrt y)\<^sup>2 \<or> x\<^sup>2 = (- sqrt y)\<^sup>2" by auto
|
60500
|
54 |
with \<open>y \<ge> 0\<close> show "x\<^sup>2 = y" by simp
|
60162
|
55 |
qed
|
|
56 |
|
|
57 |
lemma divide_non_zero:
|
|
58 |
fixes x y z :: real
|
|
59 |
assumes "x \<noteq> 0"
|
|
60 |
shows "x * y = z \<longleftrightarrow> y = z / x"
|
|
61 |
proof
|
|
62 |
assume "x * y = z"
|
60500
|
63 |
with \<open>x \<noteq> 0\<close> show "y = z / x" by (simp add: field_simps)
|
60162
|
64 |
next
|
|
65 |
assume "y = z / x"
|
60500
|
66 |
with \<open>x \<noteq> 0\<close> show "x * y = z" by simp
|
60162
|
67 |
qed
|
|
68 |
|
|
69 |
lemma discriminant_nonneg:
|
|
70 |
fixes a b c x :: real
|
|
71 |
assumes "a \<noteq> 0"
|
|
72 |
and "discrim a b c \<ge> 0"
|
|
73 |
shows "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow>
|
|
74 |
x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
75 |
x = (-b - sqrt (discrim a b c)) / (2 * a)"
|
|
76 |
proof -
|
|
77 |
from complete_square and plus_or_minus_sqrt and assms
|
|
78 |
have "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow>
|
|
79 |
(2 * a) * x + b = sqrt (discrim a b c) \<or>
|
|
80 |
(2 * a) * x + b = - sqrt (discrim a b c)"
|
|
81 |
by simp
|
|
82 |
also have "\<dots> \<longleftrightarrow> (2 * a) * x = (-b + sqrt (discrim a b c)) \<or>
|
|
83 |
(2 * a) * x = (-b - sqrt (discrim a b c))"
|
|
84 |
by auto
|
60500
|
85 |
also from \<open>a \<noteq> 0\<close> and divide_non_zero [of "2 * a" x]
|
60162
|
86 |
have "\<dots> \<longleftrightarrow> x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
87 |
x = (-b - sqrt (discrim a b c)) / (2 * a)"
|
|
88 |
by simp
|
|
89 |
finally show "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow>
|
|
90 |
x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
91 |
x = (-b - sqrt (discrim a b c)) / (2 * a)" .
|
|
92 |
qed
|
|
93 |
|
|
94 |
lemma discriminant_zero:
|
|
95 |
fixes a b c x :: real
|
|
96 |
assumes "a \<noteq> 0"
|
|
97 |
and "discrim a b c = 0"
|
|
98 |
shows "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow> x = -b / (2 * a)"
|
|
99 |
using discriminant_nonneg and assms
|
|
100 |
by simp
|
|
101 |
|
|
102 |
theorem discriminant_iff:
|
|
103 |
fixes a b c x :: real
|
|
104 |
assumes "a \<noteq> 0"
|
|
105 |
shows "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow>
|
|
106 |
discrim a b c \<ge> 0 \<and>
|
|
107 |
(x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
108 |
x = (-b - sqrt (discrim a b c)) / (2 * a))"
|
|
109 |
proof
|
|
110 |
assume "a * x\<^sup>2 + b * x + c = 0"
|
60500
|
111 |
with discriminant_negative and \<open>a \<noteq> 0\<close> have "\<not>(discrim a b c < 0)" by auto
|
60162
|
112 |
hence "discrim a b c \<ge> 0" by simp
|
60500
|
113 |
with discriminant_nonneg and \<open>a * x\<^sup>2 + b * x + c = 0\<close> and \<open>a \<noteq> 0\<close>
|
60162
|
114 |
have "x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
115 |
x = (-b - sqrt (discrim a b c)) / (2 * a)"
|
|
116 |
by simp
|
60500
|
117 |
with \<open>discrim a b c \<ge> 0\<close>
|
60162
|
118 |
show "discrim a b c \<ge> 0 \<and>
|
|
119 |
(x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
120 |
x = (-b - sqrt (discrim a b c)) / (2 * a))" ..
|
|
121 |
next
|
|
122 |
assume "discrim a b c \<ge> 0 \<and>
|
|
123 |
(x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
124 |
x = (-b - sqrt (discrim a b c)) / (2 * a))"
|
|
125 |
hence "discrim a b c \<ge> 0" and
|
|
126 |
"x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
127 |
x = (-b - sqrt (discrim a b c)) / (2 * a)"
|
|
128 |
by simp_all
|
60500
|
129 |
with discriminant_nonneg and \<open>a \<noteq> 0\<close> show "a * x\<^sup>2 + b * x + c = 0" by simp
|
60162
|
130 |
qed
|
|
131 |
|
|
132 |
lemma discriminant_nonneg_ex:
|
|
133 |
fixes a b c :: real
|
|
134 |
assumes "a \<noteq> 0"
|
|
135 |
and "discrim a b c \<ge> 0"
|
|
136 |
shows "\<exists> x. a * x\<^sup>2 + b * x + c = 0"
|
|
137 |
using discriminant_nonneg and assms
|
|
138 |
by auto
|
|
139 |
|
|
140 |
lemma discriminant_pos_ex:
|
|
141 |
fixes a b c :: real
|
|
142 |
assumes "a \<noteq> 0"
|
|
143 |
and "discrim a b c > 0"
|
|
144 |
shows "\<exists> x y. x \<noteq> y \<and> a * x\<^sup>2 + b * x + c = 0 \<and> a * y\<^sup>2 + b * y + c = 0"
|
|
145 |
proof -
|
|
146 |
let ?x = "(-b + sqrt (discrim a b c)) / (2 * a)"
|
|
147 |
let ?y = "(-b - sqrt (discrim a b c)) / (2 * a)"
|
60500
|
148 |
from \<open>discrim a b c > 0\<close> have "sqrt (discrim a b c) \<noteq> 0" by simp
|
60162
|
149 |
hence "sqrt (discrim a b c) \<noteq> - sqrt (discrim a b c)" by arith
|
60500
|
150 |
with \<open>a \<noteq> 0\<close> have "?x \<noteq> ?y" by simp
|
60162
|
151 |
moreover
|
|
152 |
from discriminant_nonneg [of a b c ?x]
|
|
153 |
and discriminant_nonneg [of a b c ?y]
|
|
154 |
and assms
|
|
155 |
have "a * ?x\<^sup>2 + b * ?x + c = 0" and "a * ?y\<^sup>2 + b * ?y + c = 0" by simp_all
|
|
156 |
ultimately
|
|
157 |
show "\<exists> x y. x \<noteq> y \<and> a * x\<^sup>2 + b * x + c = 0 \<and> a * y\<^sup>2 + b * y + c = 0" by blast
|
|
158 |
qed
|
|
159 |
|
|
160 |
lemma discriminant_pos_distinct:
|
|
161 |
fixes a b c x :: real
|
|
162 |
assumes "a \<noteq> 0" and "discrim a b c > 0"
|
|
163 |
shows "\<exists> y. x \<noteq> y \<and> a * y\<^sup>2 + b * y + c = 0"
|
|
164 |
proof -
|
60500
|
165 |
from discriminant_pos_ex and \<open>a \<noteq> 0\<close> and \<open>discrim a b c > 0\<close>
|
60162
|
166 |
obtain w and z where "w \<noteq> z"
|
|
167 |
and "a * w\<^sup>2 + b * w + c = 0" and "a * z\<^sup>2 + b * z + c = 0"
|
|
168 |
by blast
|
|
169 |
show "\<exists> y. x \<noteq> y \<and> a * y\<^sup>2 + b * y + c = 0"
|
|
170 |
proof cases
|
|
171 |
assume "x = w"
|
60500
|
172 |
with \<open>w \<noteq> z\<close> have "x \<noteq> z" by simp
|
|
173 |
with \<open>a * z\<^sup>2 + b * z + c = 0\<close>
|
60162
|
174 |
show "\<exists> y. x \<noteq> y \<and> a * y\<^sup>2 + b * y + c = 0" by auto
|
|
175 |
next
|
|
176 |
assume "x \<noteq> w"
|
60500
|
177 |
with \<open>a * w\<^sup>2 + b * w + c = 0\<close>
|
60162
|
178 |
show "\<exists> y. x \<noteq> y \<and> a * y\<^sup>2 + b * y + c = 0" by auto
|
|
179 |
qed
|
|
180 |
qed
|
|
181 |
|
|
182 |
end
|